2000
DOI: 10.1016/s0022-5347(05)67973-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence, Progression and Success in Stage Ta Grade 3 Bladder Tumors Treated With Low Dose Bacillus Calmette-Guerin Instillations

Abstract: Our study demonstrates the high progression potential of stage Ta grade 3 tumors, since nearly 50% recurred and 25% progressed to invasive disease. These results may be closely compared with the results of previous trials of stage T1 grade 3 disease. We suggest that recurrence should be detected at an early stage using long-term followup with strict observance of the surveillance protocols during a minimum 5-year tumor-free period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…Herr [6] followed 125 such patients for 15 years and observed progression in 39%, and Lebret et al [30] reported 25% progression in 4 years. Therefore, grade seems to be an important risk factor for progression.…”
Section: Discussionmentioning
confidence: 99%
“…Herr [6] followed 125 such patients for 15 years and observed progression in 39%, and Lebret et al [30] reported 25% progression in 4 years. Therefore, grade seems to be an important risk factor for progression.…”
Section: Discussionmentioning
confidence: 99%
“…Three used short courses of six weekly instillations [11][12][13], whilst the other three added a 12-month maintenance therapy [14][15][16]. The former yielded recurrence rates of 26-47% and progression rates of 9-25%; the latter studies, using maintenance therapy, gave recurrence rates of 16-23% and progression rates of 0-13.7%.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Some recent trials have demonstrated that a reduced regimen (one-third dose) may be as effective as standard dosing with fewer side effects. 26,27 Concern regarding BCG-related toxicity and disease progression has led to the study of other intravesical chemotherapeutic agents (Table 1) in the treatment of NMIBC, most notably mitomycin C (MMC). 9 However, large meta-analyses examining patients with Ta and T1 TCC have concluded that BCG is superior to intravesical chemotherapy in preventing tumor recurrence in patients at high risk 28,29 and when maintenance therapy is utilized.…”
Section: Bacillus Calmette-guerinmentioning
confidence: 99%